2023
DOI: 10.4103/sjmms.sjmms_394_22
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Type 2 Diabetes Mellitus in the General Population of Saudi Arabia, 2000–2020

Abstract: Background: The prevalence of type 2 diabetes mellitus (T2DM) has increased worldwide, including in Saudi Arabia. Objective: To systematically review the available literature and assess the pooled prevalence of T2DM in Saudi Arabia between 2000 and 2020. Methods: Observational studies that reported quantitative estimates of the prevalence of T2DM as their main outcome, included the general population of Saud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 43 publications
2
17
0
Order By: Relevance
“…Relevant research have shown that males often postpone going to the doctor when they are ill and use the less extensive array of healthcare services ( 85 ). Women are more likely than males to seek medical attention when they are unwell, which increases the likelihood that their condition will be discovered ( 86 , 87 ). Moreover, the impact of cultural expectations and societal norms on gender-specific health behaviors cannot be overlooked.…”
Section: Discussionmentioning
confidence: 99%
“…Relevant research have shown that males often postpone going to the doctor when they are ill and use the less extensive array of healthcare services ( 85 ). Women are more likely than males to seek medical attention when they are unwell, which increases the likelihood that their condition will be discovered ( 86 , 87 ). Moreover, the impact of cultural expectations and societal norms on gender-specific health behaviors cannot be overlooked.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike the A1C, literature about RIs on hemoglobin subfractions for healthy individuals is scarce. Although it is well recognized that RIs may vary from one population to another, it is important that these parameters are established for the Saudi population, which is already known to have a high prevalence of diabetes [ 44 ]. In addition to this, consanguineous marriage is very common in Saudi populations.…”
Section: Introductionmentioning
confidence: 99%
“…Advanced age and well-known susceptibility genes, such as the APOE gene encoding apolipoprotein E (ApoE), remain the most significant non-modifiable risk factors for AD ( Al-Hamdan et al, 2010 ; Walker et al, 2017 ; Jarrar et al, 2023 ). Based on numerous epidemiological studies, several modifiable vascular and metabolic factors have been linked to increasing the risk of cognitive impairment and AD, such as midlife hypertension, stroke, midlife diabetes, hyperlipidemia, obesity, and depression, in addition to other lifestyle risk factors including smoking, sleep disturbances, and low levels of education ( Al-Shammari and Al-Subaie, 1999 ; Saeed et al, 2011 ; Bennett and Thomas, 2014 ; Levin and Vasenina, 2019 ; Andreescu and Lee, 2020 ; Kuring et al, 2020 ; Tinnirello et al, 2021 ; Zhao et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…In the Kingdom of Saudi Arabia (KSA), the aging population is growing, with people aged more than 60 years, around 1.3 million in 2016. The number is expected to rise and reach more than 10 million by 2050 ( Jarrar et al, 2023 ), substantially increasing financial and emotional burdens on families and caregivers. Additionally, the lack of early detection and accurate diagnosis of neurocognitive disorders in adults is considered an issue that needs to be addressed.…”
Section: Introductionmentioning
confidence: 99%